Design and performance analysis of an industrial robot arm for robotic drilling process. Issue 1 (2nd January 2019) - Sun, Longfei; Liang, Fengyong; Fang, Lijin
Abstract : Purpose: The purpose of this paper is to present a robotic arm that can offer better stiffness than traditional industrial robots for improving the quality of holes in robotic drilling process. Design/methodology/approach: The paper introduces a five-degree of freedom (DOF) robot, which consists of a waist, a big arm, a small arm and a wrist. The robotic wrist is composed of two DOFs of pitching and tilting. A parallelogram frame is used for robotic arms, and the arm is driven by a linear electric cylinder in the diagonal direction. Double screw nuts with preload are used in the ball screw to remove the reverse backlash. In addition, dual-motor drive is applied for each DOF in the waist and the wrist to apply anti-backlash control method for eliminating gear backlash. Findings: The proposed robotic arm has the potential for improving robot stiffness because of its truss structure. The robot can offer better stiffness than industrial robots, which is beneficial to improve the quality of robotic drilling holes. Originality/value: This paper includes the design of a five-DOF robot for robotic drilling tasks, and the stiffness modeling of the robot is presented and verified by the experiment. The robotic system can be used instead of traditional industrial robots for improving the hole quality to a certain extent.